Artificial Endosymbiosis of Pedobacter sp. DDGJ Boosts the Growth Potential, Stress Resistance and Productivity of Morchella Mushrooms - Wenchang Zhang; Mantang Cao; Qi Yin; Jin Zhang; Chenhui Wang; Li Han; Yingli Cai; Xiaofei Shi; Linjing Ma; Yousif Abdelrahman Yousif Abdellah; Fuqiang Yu; Peixin He; et al. (Microbial Biotechnology, 2025)
ABSTRACT True morels are precious edible and medicinal mushrooms. The sustainable development of morel cultivation necessitates urgent breeding programmes to develop improved varieties or strains. Some soil bacteria, including Pedobacter spp., are recognised as morel's beneficial microbes. In this paper, the potential beneficial bacterium Pedobacter sp. DDGJ with minor chitinolytic activity was isolated and confirmed for improving morel's mycelial growth and identified using a combination of morphological characteristics, 16 S rRNA gene sequencing, and comparative genomics. Then, it was introduced into the hyphal cells of three cultivated Morchella strains (M. sextelata 13, M. eximia SM, and M. importuna Y2) through a confrontation culture method. The successful establishment of artificial endosymbiosis was confirmed by PCR assay, green fluorescent protein gene (gfp) localisation, and the cryo‐preparation system conjunction with high‐resolution field emission scanning electron microscopy. Laboratory assay indicated that artificial endosymbiosis of the bacterium significantly enhanced morel's growth potential, resistance to allelochemicals of 4‐coumaric acid and antagonistic capability against the pathogenic fungus Fusarium oxysporum and soil‐dominant fungus Chaetomium globosum. Moreover, the outdoor planting experiment showed significant increase in productivity among the endosymbiotic morel strains. The study provides an additional tool to improve Morchella strains with high yield and strong stress resistance.